THE EFFECT OF ATTITUDE, SUBJECTIVE NORMS, AND PERCEIVED BEHAVIOR CONTROL ON THE INTENTION OF BUYING HANNOCHS LED LIGHTING PRODUCTS - Najlir Rahmat; Halida; Khairina; Nurainun (RADJA PUBLIKA, 2024)
This research aims to analyze the influence of attitude, subjective norms and perceived behavior control on purchase intentions for Hannochs LED lighting products. Data for this research was collected through a survey method using a questionnaire as a data collection instrument. The respondents in this research were 140 respondents in the form of lecturers and employees at Malikussaleh University. This research uses a quantitative approach with multiple linear regression analysis using SPSS (Statistical Package for the Social Sciences) software. The research results show that partially Attitude has a positive and significant effect on Intention to Purchase Hannochs LED Lighting Products. Partially Subjective Norms have a positive and significant effect on Intention to Purchase Hannochs LED Lighting Products. Partially Perceived Behavior Control has a positive and significant effect on Intention to Purchase Hannochs LED Lighting Products. Simultaneously shows that Attitude, Subjective Norms, and Perceived Behavior Control Influence Intention to Purchase Hannochs LED Lighting Products